Hubungan Perilaku Caring Perawat Dengan Kecemasan Pasien Pra Operasi Di Ruang Bedah RSUD dr. H. Moh. Anwar Sumenep - Sugesti Aliftitah; Emdat Suprayitno (Fakultas Ilmu Kesehatan, 2017)
Nurse caring behavior as a moral commitment to protect, maintain and improve the dignity of patients as human beings. The problem of this study is the patient psychological symptoms of anxiety that arise when undergoing surgery, and many patients complain that the nurse is not good when providing services.This study purpose was to analyze the relation between nurse caring behavior with preoperative anxiety patient in bedah ward RSUD dr.H. Moh. Anwar Sumenep. The study design was Cross Sectional Study. The population all preoperative patients who treated in bedah ward as many as 13 nurses and preoperative patient. The sample sum a 13 nurses and 55 preoperative patients who had fill inclusion criteria by Quota Sampling technique. Independent variable is nurse caring behavior and preoperative patient anxiety as dependent variable. The results showed that most of the have good caring behavior as 7 nurses (53.8%) and most of the preoperative patients had low anxiety many as 34 patients (61.8%). The result of statistic test use Spearman rho befoud P value <α (0.002<0.05). The correlation strength r of 0.783 who has the direction that the strength of the relationship study between vareabel is sturdy. Conclusion in this study be found significant relationship between nurse caring behavior with anxiety preoperative patients in bedah ward RSUD dr. H. Moh. Anwar Sumenep 2017.